Identification of Mutations in the Canine von Willebrand Factor Gene Associated with Type III von Willebrand Disease - Rieger, M.; Schwarz, H. P.; Turecek, P. L.; Dorner, F.; Mourik, van J. A.; Mannhalter, C. (Thrombosis and Haemostasis, 1998)
In humans, type III von Willebrand disease is caused by deletions or nonsense mutations. In dogs, the underlying genetic defects have not been determined yet. We searched for the genetic defect in four related type III deficient Dutch Kooiker dogs obtained from one breeder. Mutation analysis was performed with total RNA isolated from platelets or whole blood. The complete coding region of the vWf gene was amplified by RT-PCR and sequenced by the cycle sequencing technique. Two homozygous mutations were found, a G→A transition at the first position of the donor splice site sequence of intron 16 (TGgtaagt→TGataagt) and a missense mutation at nt 208 (G→A) (1). The splice site defect resulted in the generation of a transcript containing 46bp of intron sequence and a stop codon at amino acid position 729 in the propeptide region of the vWf protein. This mutation seems to be causative for the type III phenotype. The effect of the missense mutation in exon 3 which causes a change of Val to Ile on the vWD phenotype is unclear. Probably, this transition represents a polymorphism occurring in Dutch Kooiker dogs. Both mutations were not present in 5 healthy mongrel dogs.Parts of this paper were presented at the 39th annual meeting of the American Society of Hematology (ASH), December 5-9, San Diego, USA